Telaah Kritis Marital Satisfaction dalam Perspektif al Quran dan Psikologi Positif - Dewi Purnama Sari (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
A Critical Study of Marital Satisfaction in the Perspective of the Qur’an and Positive PsychologyMarital satisfaction or getting marital satisfaction is everyone's dream. In fact, not all couples get marital satisfaction. This study aims to discuss the concepts and factors that influence marital satisfaction in the perspective of the Qur’an and positive psychology by using a library research approach. The results of the discussion show that marital satisfaction in the perspective of the Qur’an means happiness and peace which is filled with love and is based on religious values. In the study of positive psychology, marital satisfaction is happiness and pleasure in undergoing a marriage based on knowledge alone. Marital satisfaction in the perspective of the Qur’an is influenced by psycho-theo-anthropocentric and anthropocentric factors, while in the perspective of positive psychology it is only influenced by anthropocentric factors